The Sockets Networking API : UNIX® Network Programming Volume 1, Third Edition - Stevens, W.; Fenner, Bill; Rudoff, Andrew (Addison-Wesley Professional, 2003)
UNIX Network Programming, Volume 1: The Sockets Networking API, Third Edition "Everyone will want this book because it provides a great mix of practical experience, historical perspective, and a depth of understanding that only comes from being intimately involved in the field. I've already enjoyed and learned from reading this book, and surely you will too." --Sam Leffler The classic guide to UNIX networking APIs... now completely updated! To build today's highly distributed, networked applications and services, you need deep mastery of sockets and other key networking APIs. One book delivers comprehensive, start-to-finish guidance for building robust, high-performance networked systems in any environment: UNIX Network Programming, Volume 1, Third Edition. Building on the legendary work of W. Richard Stevens, this edition has been fully updated by two leading network programming experts to address today's most crucial standards, implementations, and techniques. New topics include: POSIX Single UNIX Specification Version 3 IPv6 APIs (including updated guidance on IPv6/IPv4 interoperability) The new SCTP transport protocol IPsec-based Key Management Sockets FreeBSD 4.8/5.1, Red Hat Linux 9.x, Solaris 9, AIX 5.x, HP-UX, and Mac OS X implementations New network program debugging techniques Source Specific Multicast API, the key enabler for widespread IP multicast deployment The authors also update and extend Stevens' definitive coverage of these crucial UNIX networking standards and techniques: TCP and UDP transport Sockets: elementary, advanced, routed, and raw I/O: multiplexing, advanced functions, nonblocking, and signal-driven Daemons and inetd UNIX domain protocols ioctl operations Broadcasting and multicasting Threads Streams Design: TCP iterative, concurrent, preforked, and prethreaded servers Since 1990, network programmers have turned to one source for the insights and techniques they need: W. Richard Stevens' UNIX Network Programming . Now, there's an edition specifically designed for today's challenges--and tomorrow's.